2017
DOI: 10.1111/jopy.12354
|View full text |Cite
|
Sign up to set email alerts
|

Self‐ and informant perceptions of psychopathic traits in relation to the triarchic model

Abstract: These findings suggest that participants are willing and able to disclose psychopathic personality traits in research settings under conditions of confidentiality. Nonetheless, accounting for response style is potentially useful when using self-report measures to examine the nature and correlates of psychopathic traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 70 publications
1
23
3
Order By: Relevance
“…This finding is consistent with studies on adaptive trait models showing higher self-other agreement on conscientiousness and extraversion (Connelly & Ones, 2010). There are exceptions, however, in which relatively higher agreement has been found on antagonistic traits (i.e., maladaptive low agreeableness), compared to other maladaptive trait domains-a pattern that would not be expected based on accuracy theories of normal range traits (Kelley et al, 2018;Sleep, Lamkin, Lynam, Campbell, & Miller, in press). These mixed findings indicate that a meta-analysis of the growing literature would be useful.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…This finding is consistent with studies on adaptive trait models showing higher self-other agreement on conscientiousness and extraversion (Connelly & Ones, 2010). There are exceptions, however, in which relatively higher agreement has been found on antagonistic traits (i.e., maladaptive low agreeableness), compared to other maladaptive trait domains-a pattern that would not be expected based on accuracy theories of normal range traits (Kelley et al, 2018;Sleep, Lamkin, Lynam, Campbell, & Miller, in press). These mixed findings indicate that a meta-analysis of the growing literature would be useful.…”
supporting
confidence: 88%
“…Our compilation of over 50 studies of self-other agreement on personality disorder reported a range of rank-order correlation sizes from r = .12 to r = .90, with a median of r = .35 (see Table 1). There are college, clinical, and community samples presenting a range of effect sizes from small (e.g., Tackett et al, 2013;Yalch & Hopwood, 2016;Zimmerman et al, 1988) to large (e.g., Coolidge et al, 1995;Few et al, 2013;Kelley et al, 2018;Miller et al, 2011).…”
Section: Rank-order Agreementmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a push for different modes of assessment of external correlates should be made (e.g., interview and collateral information). Generally, monomethod assessment can inflate effect sizes, and initial research has suggested that differing forms of assessment can influence the strength of association between Boldness and other variables (Kelley, Edens, Mowle, & Sörman, 2015). This limitation is present in the current study and extends across much of the triarchic psychopathy research.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, for other types of psychological difficulties, such as alcohol use among college students, self-ratings and informant ratings demonstrate no mean difference (Borsari & Muellerleile, 2009), although they are not necessarily redundant. It is worth noting that the utility of informant report has been demonstrated by findings of incremental validity over self-report and/or interview-based ratings in predicting numerous outcomes, including social behavior and psychological distress among psychiatric inpatients (Ready, Watson, & Clark, 2002), prior episodes of major depression (Galione & Oltmanns, 2013), alcohol consumption (Whitford et al, 2009) and intimate partner violence (Jones & Miller, 2012) among community members, and antisocial behavior among undergraduates (Kelley, Edens, Mowle, & Sörman, 2015).…”
mentioning
confidence: 99%